2011
DOI: 10.1007/s10517-011-1234-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Characteristics of the Immune System in CBA and C57Bl/6g Mice

Abstract: We studied peculiarities of morphofunctional organization of the immune system in C57Bl/6g and CBA mice differing by their susceptibility to various types of infectious agents. The revealed differences in the structure of lymphoid organs, T lymphocyte subpopulation ratio and their differentiation into Th1/Th2 cells after mitogen stimulation drove us to a conclusion on genetically determined regularities in the development of the immune response in these animal strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The half-life of Nrf2 is 7.5 to 15 min, [33][34][35] and it is regulated by Keap1-dependent ubiquitination and degradation. 36 Nrf2 is sequestered in the cytosol by Keap1, which regulates Nrf2 ubiquitination via Cul3-Keap1 complex. Under oxidative stress, the Cul3-Keap1-E3 ligase is inhibited, allowing Nrf2 translocation to the nucleus, binding to antioxidant response elements and initiating transcription of antioxidant enzymes.…”
Section: Hypertensionmentioning
confidence: 99%
“…The half-life of Nrf2 is 7.5 to 15 min, [33][34][35] and it is regulated by Keap1-dependent ubiquitination and degradation. 36 Nrf2 is sequestered in the cytosol by Keap1, which regulates Nrf2 ubiquitination via Cul3-Keap1 complex. Under oxidative stress, the Cul3-Keap1-E3 ligase is inhibited, allowing Nrf2 translocation to the nucleus, binding to antioxidant response elements and initiating transcription of antioxidant enzymes.…”
Section: Hypertensionmentioning
confidence: 99%
“…The CBA and C57BL/6 mouse strains develop different response to infection and radiation [20,22]. Some authors suggested that the observed phenomena might be explained by the differences in T-and B-lymphocytes [23], and peculiarities of T-cell differentiation [27]. Our results indicate that CBA and C57BL/6 mice vary in hemoglobin content in RBC, in number and size of platelets and in number of neutrophils.…”
Section: Discussionmentioning
confidence: 49%
“…The available data indicate that these two strains can be considered as contrasting ones regarding function of their immune system [20,22,23]. And both strains are used for studying the effects of IVIG [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a predominance of cellular elements (monocytes, macrophages, Kupffer cells) in the mononuclear phagocyte system (bone marrow-peripheral blood-liver) of C57BL/6 mice. Subsequently, this reflects a genetically determined higher power (quantitatively) of the system of mononuclear phagocytes in C57BL/6 mice compared to CBA mice [13]. It is believed that classical type activation (M1) is more characteristic in macrophages of C57BL/6 mice in contrast to the alternative one in macrophages of BALB/c and CBA mice [14][15][16].…”
Section: Introductionmentioning
confidence: 96%